INTERAKSI PSEUDOMONAD PENDARFLUOR INDIGENUS DENGAN Glomus aggregatum TERHADAP SERANGAN PENYAKIT BATANG BERLUBANG DAN PERTUMBUHAN TANAMAN TEMBAKAU - Gita Pawana; - Syekhfani; Tini Surtiningsih; Wiwiek Sri Wahyuni (Agrovigor, 2012)
Properties are favorable for the growth of plants from mycorrhizal arbuscular fungi and pseudomonads fluorescenct still need the wider examine,  the positive interaction that may be obtained from their association. The purpose of this study was to examine the interaction of Pseudomonas fluorescens Pfim20 with Glomus aggregatum in the rhizosphere of tobacco and evaluate whether the interaction can increase of growth and suppress hollow stalk disease. The method of research is evaluation of antagonistic P. fluorescens Pfim20 towards Pectobacterium carotovorum, followed by green house experiment. The results obtained,  the association of P. fluorescens Pfim20 with G. aggregatum positive interaction, on the presence or the absence of association between of P. fluorescens Pfim20 with G. aggregatum there are not level of disease severity and progression of hollow stalk disease, positive interaction between P. fluorescens Pfim20 with G. aggregatum can increase the uptake of phosphate, but can not give a higher biomass.